Entre os meandros da tolerância : cristãos-novos, judeus e as especificidades da institucionalização do judaísmo no contexto inter-religioso do Brasil holandês (1630-1654) - Santos, Nelson Santana (2017)
This work aims to establish a (mainly) historical look at the Jewish religiosities experienced between 1630 and 1654, in the Captaincy of Pernambuco, then under the military-political domination of the Dutch. It is a sui generis moment in which, even for a brief interregnum, freedom of religious conscience was granted to all - including the Jews, persecuted in various parts of the world at that time. In this differentiated scenario, Catholics, Protestants and Jews shared the same political and legal space. This true harbinger of religious toleration attracted many Jews from other countries, encouraged New Christians who lived there to re-embrace their ancient faith and culminated in the institutionalization of the first Jewish community in the Americas. With a special emphasis on the participation of New Christians, the main focus of the research is to investigate the extent to which the freedom of religious consciousness and the true cultural background existing in that region engendered the necessary conditions for the emergence of (a) religious experience(s) of Judaism differentiated from those occurring in other historical contexts, as well as to identify at a minimum what these possible specificities would be.